(untitled) (Raparin Journal of Humanities (RJH), 2024)
Residential projects with necessary infrastructure and social services offer a distinct social and urban environment and better living conditions compared to the old neighborhoods. These projects support the continuity of family relations and social activities through gatherings in recreational areas and children’s playgrounds, offering a viable solution for the residential gap caused by the disparity between the number of residential units and population growth. The research analyzes the nature of residential projects in Kalar city, focusing on their geographical distribution, reasons for their emergence and development, obstacles faced, and their role in addressing the housing shortage. The first part of the research is the theoretical framework. The second part covers the geographical distribution of residential projects in the research area, encompassing 22 projects and 23,376 residential units as of 2023. The third part explains the reasons behind construction and increase of these projects. The fourth part presents an analysis for the distribution of the projects using GIS. The fifth part evaluates the inhabited projects in terms of density and communal services either in the current site plans or in the planning criteria based on population and residential unit numbers. The final part examines the role of these projects in solving the residential gap in Kalar, where 34,663 families are accommodated in 32,498 residential units as of 2023. The research concludes with findings and recommendations